Biografi Tokoh Lokal sebagai Sumber Belajar IPS: Studi Nilai Kewirausahaan pada Kisah Siti Lailatul Barokah - Chorilifa Safe Naibobe; I Putu Sriartha; I Wayan Kertih (Universitas Hamzanwadi, 2026)
The role of women in sustaining family economic resilience has become increasingly significant, particularly within small-scale and informal economic sectors. However, narratives of women's struggles and achievements in building economic independence are rarely utilized as contextual learning resources in schools. This study aims to analyze the life journey and economic struggles of Siti Lailatul Barokah as a female entrepreneur and to examine the educational values embedded in her biography that can be used as learning resources for Social Studies (IPS) at the junior high school level. This research employs a qualitative approach using a biographical method. Data were collected through documentation studies of the biographical book, interviews, and relevant literature reviews. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that the life journey of Siti Lailatul Barokah reflects the dynamic struggle of women in developing economic resilience through perseverance, risk-taking, adaptability, and the ability to recognize business opportunities within their social environment. Furthermore, her life story contains educational values such as independence, responsibility, persistence, and entrepreneurial spirit, which are relevant to be developed as learning resources in junior high school Social Studies. Therefore, the biography of local figures can serve as contextual learning material that not only enriches students' knowledge but also instills character values and a deeper understanding of economic activities within society.